Perfil bioquímico sérico e hematológico de eqüinos submetidos à prova de Team Penning - Miranda, Renata Lima de (2009)
CHAPTER II: Knowledge of serum biochemical changes related to exercise is needed because these changes reflect the function of different systems and the type of energy used. Analyzed separately, the clinical signs of distinct muscular alterations have a limited diagnostic value and require the use of complementary laboratory exams. Such exams are also used to evaluate the animal s training, clinical state or athletic capacity. This study determined the serum concentrations of proteins, metabolites, minerals and serum enzymes in equines subjected to team penning contests, correlating these data with sex and frequency of physical activity. A puncture was made in the external jugular vein to collect five mL of blood from 29 equines, 18 males and 11 females, at rest (Group I) and after exercising (Group II). The biochemical serum analyses were carried out with a Micronal B-280 spectrophotometer using commercial kits and an automatic multichannel analyzer (Abbott Diagnostics - ARCHITECT c8000) using specific kits. The animals were divided into Groups A, B, C and D according to the number of times they participated in the contest. The serum albumin concentrations, A:G ratio and iron declined significantly (p<0.05) after exercising, unlike the concentrations of total proteins, globulins, total calcium, uric acid, urea, creatinine, aspartate aminotransferase (AST), lactate dehydrogenase (LDH) and creatine kinase (CK), which increased. Females showed a higher increase of creatinine. Moreover, the rise in total protein, globulins, creatinine, AST, LDH and CK levels differed among groups A, B, C and D. It was concluded that the Team Penning contest causes alterations in the biochemical serum profile of equines, and that sex and the number of participations in the contest are interferential variables. CHAPTER III: Variations in hematologic parameters are used to assess the degree of training or clinical state of the animal. The hematologic evaluation of equines at rest has been an object of study in order to establish a correlation with training or athletic capacity. The purpose of this study was to evaluate the hematologic profile of horses subjected to Team Penning competitions, correlating sex and frequency of physical activity. Three milliliters of blood were drawn through a puncture made in the external jugular vein from 29 equines, 18 males and 11 females at rest (Group I) and after exercising (Group II). The blood samples were processed in an ABC VET automated veterinary hematology analyzer (Horiba ABX Diagnostics). The animals were divided into Groups A, B, C and D according to the number of times they participated in the competition. The values of globular volume, hemoglobin, erythrocytes, rod-shaped and segmented neutrophils, and monocytes were found to increase after the physical exercise, unlike the number of lymphocytes and eosinophils, which decreased. A comparison of the before/after exercise correlations showed no significant differences (p<0.05) between males and females. In addition, it was found that the value of the GI/GII ratio for the globular volume, hemoglobin and number of erythrocytes varied according to the frequency of the exercise. It was concluded that the Team Penning competition produces hematologic alterations in equines, which are affected by the frequency of exercising, regardless of sex.